A novel method for estimating the real-time dullness of tri-cone oil drill bits. (January 2020) - Abbas, Rafid K.; Ghanbarzadeh, Ali; Hassanpour, Ali
Highlights: The dullness of the tri-cone bit obtained from the new modified model in this work is compared to the in-situ real-time bit tooth wear for a number of wells in southern Iraq, where a reasonable agreement was observed. The presented work could be extended to other types of drill bits such as Polycrystalline Diamond Compact (PDC) bits. Abstract: It is vital to anticipate the durability of drill bits for all drilling operations to prolong the drilling processes and reducing economic losses. Many attempts have been made to handle this issue by assessing the parameter of specific energy of the bits generated during drilling along with well logs and geophysical analyses. Although these techniques could provide acceptable precautions of the dullness of bit cutters, lack of consideration of material properties of the rock and the bit is their main shortcoming which could result in misleading interpretations. The present study deals with the development of a wear model for Tri-cone bits based on the concept of three body abrasive wear taking into account two main factors, rock hardness and the hardness of the materials forming the Tri-cone drill bit. Other parameters that have significant effect are also considered, such as weight on bit, penetration rate, rotation speed and the required time to penetrate an interval depth. In this research, the bit wear quantified by the new developed model is compared with the in-situ dullness of the drill bit for a number of wells being excavated in southern Iraq, where a reasonable agreement was observed. The present work could be extended to other oil wells and applied on other types of drill bits to confirm the validation of the new model.